2020
DOI: 10.1038/s41598-020-70026-w
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic drug combinations and machine learning for drug repurposing in chordoma

Abstract: Chordoma is a devastating rare cancer that affects one in a million people. With a mean-survival of just 6 years and no approved medicines, the primary treatments are surgery and radiation. In order to speed new medicines to chordoma patients, a drug repurposing strategy represents an attractive approach. Drugs that have already advanced through human clinical safety trials have the potential to be approved more quickly than de novo discovered medicines on new targets. We have taken two strategies to enable th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…The PI3K/mTOR targeting drugs sapanisertib and vistusertib showed efficacy in our organoid screenings (Figure 3). Both drugs have been found to be effective in chordoma cell lines 23,49 . Our screening additionally identified other PI3K/mTOR targeting drugs such as apitolisib and omipalisib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/mTOR targeting drugs sapanisertib and vistusertib showed efficacy in our organoid screenings (Figure 3). Both drugs have been found to be effective in chordoma cell lines 23,49 . Our screening additionally identified other PI3K/mTOR targeting drugs such as apitolisib and omipalisib.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR targeting drugs such as lapatinib have shown some efficacy in controlling disease and are approved for use in EGFR positive chordomas 10,51 . Additional EGFR targeting drugs that have been tested in clinical trials for chordoma include erlotinib, linsitinib, afatinib, and the monoclonal antibody cetuximab 48,49 . We observed moderate efficacy of the EGFR targeting drug gefitinib in 3/7 samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiple drugs can be used to synergistically impact one target or pathway, such as GKT136901 and L-NAME working on NOX4 and co-target NOS (122). Several computational methods are available to investigate synergistic effects between drugs for therapy (123)(124)(125)(126). In a computational development challenge to find cancer drug combinations, 160 teams developed computational methods to find synergistic drug combinations (126).…”
Section: Overview Of Drug Repurposingmentioning
confidence: 99%
“…Based on the validation results, authors concluded that model could predict new drugs for psoriasis, with the highest prediction scores for budesonide (a corticosteroid, currently used to treat asthma and inflammatory bowel disease) and hydroxychloroquine (an antimalarial drug that is also used to treat lupus and rheumatoid arthritis). Anderson et al 129 used Bayesian ML models for drug repurposing in chordoma. Of the available data, the mTOR inhibitor AZD2014 was indicated as the most potent against chordoma cell lines (IC 50 0.35 μM U‐CH1 and 0.61 μM U‐CH2).…”
Section: Drug Design In Practicementioning
confidence: 99%